Alzheimer's disease drug development pipeline: 2025 - Jeffrey L. Cummings; Yadi Zhou; Garam Lee; Kate Zhong; Jorge Fonseca; Amanda M. Leisgang‐Osse; Feixiong Cheng (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2025)
Abstract Clinical trials for Alzheimer's disease (AD) must be registered on clinicaltrials.gov. The registry presents a variety of types of information related to the planned clinical trial. We assess clinicaltrials.gov to document and compare aspects of drug development across the AD pipeline. Currently, there are 138 drugs being assessed in 182 clinical trials in the AD pipeline. Biological disease‐targeted therapies (DTTs) comprise 30% of the pipeline; small molecule DTTs account for 43% of the pipeline; drugs addressing cognitive enhancement account for 14% of the pipeline; and drugs aiming to ameliorate neuropsychiatric symptoms in participants with AD contribute 11% of the pipeline. Biomarkers are among the primary outcomes of 27% of active trials. Repurposed agents represent 33% of the pipeline agents. The pipeline has more trials and more drugs compared to the 2024 pipeline. Highlights The 2025 Alzheimer's disease drug development pipeline hosts 182 trials and 138 novel drugs. The 2025 Alzheimer's disease drug development pipeline is diverse, with agents that address 15 basic disease processes. The 2025 Alzheimer's disease drug development pipeline has more trials and more drugs than the 2024 pipeline. Biomarkers play an important role in current trials to determine trial eligibility and as outcomes of trials. Repurposed agents comprise approximately one‐third of the agents and trials in the 2025 Alzheimer's disease drug development pipeline.